Two British Columbia University Colleges and the Process of Economic Globalization - Levin, John S. (Canadian Journal of Higher Education, 2003)
This qualitative investigation identifies a condition of frenetic change experienced by organizational members at two university col- leges in British Columbia, Canada, during the past decade. Prominent outcomes of the formal designation of five former community colleges as university colleges included curricular change and the evolution of a new institutional mission. The brief history of the university colleges of British Columbia parallels the process of economic globalization in the province of British Columbia, and the responses of managers and faculty at university colleges indicate that globalization influenced the formation and functioning of these institutions.